The Effect of Using (Hawkins) Strategy in the Achievement of the Primary Fifth Class in Mathematics (Journal of the College of Basic Education, 2019)
The objective of the current study was to identify the effect of strategy of Hawkins on the creative thinking and achievement of the primary fifth class in mathematics.To verify the current research objective, the researcher formulated the following hypothesis:- there was no statistically significant difference at the level of significance (P>0.05) between the average scores of the experimental group students who study using the Hawkins strategy and the average scores of the control group students who study in the usual way in the achievement test.The current research was limited to the students of the primary fifth class in Al-Kufa Primary Girls School of the Directorate of Education of Baghdad/ The Third Al-Rusafa/ second term of the academic year 2018 AD- 2019 AD and on the chapters (seventh, eighth, ninth, tenth and eleventh) of the book of mathematics scheduled. The researcher chose two divisions (out of three people for the primary fifth class) in a simple random drawing method. Section (C) was chosen to represent the experimental group studying mathematics according to the Hawkins’ strategy and section(B) to represent the control group that studies mathematics according to the usual method. The sample size was (48) students with (25) students in the experimental group and (23) students in the control group.The researcher selected experimental design with partial control of two groups (experimental and control) and the post-test. The two research groups were rewarded with variables (previous knowledge test, previous achievement, intelligence test scores).The researcher studied the two research groups and formulated behavioral aims for the five chapters and for the three levels of Bloom’slevels (recall, application, comprehension), reached (121) aims. Furthermore, the researcher prepared a post-achievement test consisting of (30) multi-choice types with four alternatives. The validity and stability of the test and calculation of the coefficient of difficulty and discriminating force and the effectiveness of the wrong alternatives of the test were examined. The researcherused the Kuder-Richardson equation (R20-k) to calculate the coefficient of the achievement test stability for the paragraphs and the t-test for two independent samples for data processing.The results indicated that there was a statistically significant difference at the level of (0,05) between the average scores of the experimental group and the control group and for the experimental group that studied the subject according to the strategy (Hawkins) in the achievement test.The researcher concluded that Hawkins' strategy had an impact on raising the level of achievement of the primary fifth class in mathematics.The researcher made several recommendations, including the use of Hawkins' strategy in teaching mathematics for the primary fifth class, and the training of teachers of mathematics in the primary stage on how to use this strategy,and the researcher suggested conducting similar studies for the current study on different subjects and another classes, and other variables not addressed by the current study.